2020
DOI: 10.2147/ndt.s278248
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between SIRT Genetic Polymorphisms and Postpartum Depressive Symptoms in Chinese Parturients Who Had Undergone Cesarean Section

Abstract: Objective To investigate the association of genetic polymorphisms of SIRT with postpartum depressive symptoms and analyze the risk factors for postpartum depressive symptoms in women following cesarean section. Methods A total of 368 Chinese woman undergoing cesarean section were enrolled in this study. A cutoff of ≥10 for the Edinburgh Postnatal Depression Scale identified postpartum depressive symptoms. Genotypes of SIRT1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Total EPDS scores, which ranged from 0 to 30 points, were the sum of the scores from each item. To determine the incidence of PPD, a cutoff of 10 or more points was defined as positive for PPD according to the published recommendations . Furthermore, to evaluate depressive symptoms among the 2 cohorts, we also analyzed the EPDS score as a continuous variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total EPDS scores, which ranged from 0 to 30 points, were the sum of the scores from each item. To determine the incidence of PPD, a cutoff of 10 or more points was defined as positive for PPD according to the published recommendations . Furthermore, to evaluate depressive symptoms among the 2 cohorts, we also analyzed the EPDS score as a continuous variable.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the incidence of PPD, a cutoff of 10 or more points was defined as positive for PPD according to the published recommendations. 34 , 35 , 36 Furthermore, to evaluate depressive symptoms among the 2 cohorts, we also analyzed the EPDS score as a continuous variable. This involved comparing the change in this parameter between the 2 groups from baseline (the day before surgery) to the end points.…”
Section: Methodsmentioning
confidence: 99%
“…Research on a Japanese population showed similar results that SNP rs1245800, rs4746720 (SIRT1) and rs10997875 (SIRT1) were discovered to be associated with suicide and MDD [ 72 , 73 ]. Not only SIRT1, SNPs in SIRT2 were also found to be related to the risk of postpartum depressive symptoms [ 74 ]. Studies have shown that MDD is a disease relevant to inflammation and redox homeostasis.…”
Section: Histone Modification In Mddmentioning
confidence: 99%
“…Among the mainstream hypotheses of the cause of depression, the hypothesis of immune and inflammation has been a hot spot in studying its pathological mechanism ( Sharma, 2016 ; Leonard, 2018 ; Beurel et al, 2020 ). Polymorphism studies have shown that SIRT2-related genes are associated with postpartum depression ( Luo et al, 2020 ) and AD depression ( Porcelli et al, 2013 ).…”
Section: Sirtuin 2 and Neuroinflammatory Disordersmentioning
confidence: 99%